Electrocatalytic proton and water reduction by a Co(III) polypyridyl complex. (1st February 2019) - Rai, Surabhi; Majee, Karunamay; Raj, Manaswini; Pahari, Asit; Patel, Jully; Padhi, Sumanta Kumar
Graphical abstract: A fac -cobalt(III) alcoholate complex was characterized by spectroscopic and electrochemical techniques which acts as a robust hydrogen evolving catalyst both in organic and aqueous media. The spectral investigations reveal that dechelation followed by protonation at the pendant pyridyl base is the key parameter for the proton reduction. Based on the electrochemical and spectroscopic data a plausible mechanism has been proposed. Abstract: A facial cobalt(III) polypyridyl complex was characterized by several spectroscopic and electrochemical techniques and utilized as a robust hydrogen evolving catalyst in both organic and aqueous media. The complex exhibits reasonably high electrocatalytic activities towards proton reduction in organic medium by using acetic acid as external proton source and achieves a TOF of 699 s −1 . The complex also shows fair water reduction in phosphate buffer pH 7 by achieving TOF of 413 mol H2 (mol cat) −1 h −1 over 2 h of CPE. The catalyst shows high stability in lower pH by performing water reduction up to pH 4, where its catalytic activity increases with decrease in pH as inferred from CV as well as CPE experiments done in different pH solutions. The catalytic cycle goes up to four cycles with decrease in activity of the catalyst in each subsequent cycle, which indicates a partial decomposition of the catalyst in each cycle. The pKa value for [Co III (L)( 2 LH)S] 2+ ⇆ [Co III (L)( 2 L)S] + was observed at 4.7 (where 2 LH and S are, the bidentate protonated form of dechelated N atom of ligand L and solvent or water repectively). Based on the Pourbaix plot, other spectroscopic studies and previous reports, the plausible mechanism for proton reduction and water reduction has been proposed.